Cultural Values in the Javanese 'Temu Manten' Ceremony Process: A Case Study in Simalungun Regency - Ramadhayani, Nanda; Perangin-angin, Alemina Br. (Aksara: Jurnal Bahasa dan Sastra, 2024)
The "Temu Manten" tradition is a Javanese tradition, one of which is practiced in the Simalungun Regency. This tradition is usually followed when someone wants to marry off their son or daughter. "Temu Manten" is also often referred to as the "Panggih Ceremony," which means the ceremony of the meeting of the prospective groom and bride at the bride's residence. The research aims to describe the values embedded in the traditional Javanese culture of "Temu Manten" in the Simalungun Regency. The researcher used a qualitative descriptive research method. Data collection involved face-to-face interviews with cultural experts and wedding guides at several pavilions in the Simalungun Regency, as well as online interviews. The study's results show that in the implementation of the "Temu Manten" tradition in the Simalungun Regency, there are several processes such as "Tukar Kembar Sanggan" and "Mayang," "Balangan Gantal," "Ranupada," "Sinduran," "Pangkon Timbang," "Kacar Kucur," "Dulangan," "Mapag Besan," and "Sungkem." However, before these sequences are carried out, several preliminary processes must be performed, such as "Bedol Kembar Mayang," which is the process of throwing the "Mayang Kembar" on the roof of the house, symbolizing the return of plants from heaven to the gods. Each step of the "Temu Manten" ceremony has its own meaning, which is a prayer for the newlyweds. The survey results above can be concluded that the betrothal ceremony in the Simalungun Regency has distinctive characteristics. In this region, the betrothal ceremony involves a unique "bodol kembar mayang" ritual, which is used as a symbol of the return of sacred plants to the gods or as an expression of gratitude to the Creator. Additionally, it marks the first meeting of the bride and groom through the "Bubak Kawah" marriage, signifying the first child-in-law or the final closing of the in-law relationship. Keyword: Marriage, Temu Manten, Cultural Values